Global, regional, and national trends and burden of hypertensive disorders in pregnancy among women of childbearing age from 1990 to 2021 - Zhongyun Tang; Chao Ma; Jin Liu; Chongdong Liu (Frontiers in Global Women's Health)
BackgroundHypertensive disorders of pregnancy (HDP) are a significant cause of maternal and perinatal morbidity and mortality worldwide. This study aims to use the Global Burden of Disease 2021 database to analyze the prevalence trends and disease burden of HDP across the globe from 2019 to 2021.MethodsWe analyzed four key metrics related to HDP (prevalence, incidence, mortality, and DALYs) using data from the GBD Database. Trends were assessed using the estimated annual percentage change (EAPC) and changes in disease burden.ResultsIn 2021, global HDP prevalence cases, incidence cases, mortality cases, and DALYs were 3.51 million, 18.00 million, 37.58 million, and 2.44 million, respectively, with percentage changes of 14%, 15%, −29%, and −29% over the study period. Prevalence and incidence rates increased (EAPCs: −0.7 and −0.67), while mortality and DALYs rates decreased (EAPCs: −2.29 and −2.28). Low Socio-demographic Index (SDI) regions had the highest HDP burden, accounting for about half of the global total. The 25–29 age group had the highest incidence cases.ConclusionOver the past 32 years, HDP prevalence cases and incidence cases have risen globally, but death cases and DALYs cases have significantly decreased, particularly in low SDI regions and the 25–29 age group. The global HDP burden is higher in regions with lower SDI. Our findings highlight regional and age-related disparities in HDP, providing a basis for targeted interventions and prevention strategies.